Low levels of hybridization across two contact zones among three species of woodpeckers (Sphyrapicus sapsuckers). (8th July 2016) - Seneviratne, Sampath S.; Davidson, Peter; Martin, Kathy; Irwin, Darren E.
Abstract : Three species of closely related woodpeckers (sapsuckers; Sphyrapicus ) hybridize where they come into contact, presenting a rare 'λ‐shape' meeting of hybrid zones. Two of the three arms of this hybrid zone are located on either side of the Interior Plateau of British Columbia, Canada bordering the foothills of the Coast Mountains and the Rocky Mountains. The third arm is located in the eastern foothills of the Rocky Mountains. The zones of hybridization present high variability of phenotypes and alleles in relatively small areas and provide an opportunity to examine levels of reproductive isolation between the taxa involved. We examined phenotypes (morphometric traits and plumage) and genotypes of 175 live birds across the two hybrid zones. We used the Genotyping By Sequencing (GBS) method to identify 180 partially diagnostic single nucleotide polymorphisms (SNPs) to generate a genetic hybrid index (GHI) for each bird. Phenotypically diverged S. ruber and S. nuchalis are genetically closely related, while S. nuchalis and S. varius have similar plumage but are well separated at the genetic markers studied. The width of both hybrid zones is narrower than expected under neutrality, and analyses of both genotypes and phenotypes indicate that hybrids are rare in the hybrid zone. Rarity of hybrids indicates assortative mating and/or some form of fitness reduction in hybrids, which might maintain the species complex despite close genetic distance and introgression. These findings further support the treatment of the three taxa as distinct species.